An Analysis of the Impact and Efficacy of Online Emotional Intelligence Coaching as a Support Mechanism for University Students - Carthy, Aiden; Chalmers, Wyndham; Guiry, Eoghan; Owende, Philip (Frontiers in Education, 2022)
As a consequence of the COVID-19 pandemic, many college courses have pivoted to complete online delivery and colleges are also tasked with providing student supports online. It is likely this transition will last beyond any COVID-19 specific restrictions, therefore this small-scale, exploratory study examined the efficacy and impact of the provision of a five week online emotional intelligence (EI) coaching to a cohort of Irish university students (n=19) studying at Technological University Dublin (TU Dublin). Results revealed that the average overall level of EI increased for participants following the coaching programme. Students reported that they believed the programme provided emotional support and that it also enabled them to manage academic stress more effectively and ultimately that engagement with the programme had a positive impact on their academic engagement. Taken collectively, the results of this study suggest that whilst EI coaching can be successfully delivered online, where possible, a blended approach may be optimal. However, as this is a novel and exploratory study, further confirmatory research is recommended.